HUBUNGAN KEPATUHAN MINUM OBAT TERHADAP KONTROL TEKANAN DARAH PASIEN HIPERTENSI DI PUSKESMAS MANGGIS PROVINSI BALI - Purnamayanti, Ni Kadek Diah; Puspitarini, Ni Kadek; Aryawan, Kadek Yudi (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023, 2023)
Hypertension is a chronic disease that requires long-term treatment. This has an impact on the size of national health financing. In an effort to anticipate costs related to complications, it is necessary to evaluate treatment adherence in the short and long term. This study aims to analyze the relationship between medication adherence and blood pressure control as a short-term outcome of hypertension management at the primary care level. The research method uses a cross sectional design. The research was conducted at the Manggis Health Center with a total sample of 32 people. The sampling technique used is purposive sampling. The measurements used demographic questionnaires, observation sheets for blood pressure checks, and the MMAS-8 questionnaire in Indonesian. Statistical test resultsusing Chi square found p = 0,016 (p<0,05) so there is a relationship between medication adherence and blood pressure control in hypertensive patients. The therapeutic effect of ACE inhibitor and calcium channel blocker directly make the blood vessels relax and wider. The characteristics of hypertensive patients at the Manggis Health Center are mostly the elderly population, women, most do not smoke, and do not have comorbid diabetes. However, proactive prognosis projection is needed. The conclusion in this study is that there is a relationship between medication adherence and blood pressure control in hypertensive patients at the Manggis Health Center.